Integration of internet for teaching purposes: perceptions of ESL teachers as TESL postgraduates in UPM, Malaysia - Saadat, Uranus; Hussin, Habsah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The main purpose of this study was to find the perceptions of ESL teachers as local TESL postgraduates in University Putra Malaysia (UPM) regarding the integration of Internet for instructional purposes. A simple random sampling was used to select 94 ESL teachers from this university. A mixed-method design has been implemented to seek this study through a questionnaire and an interview taken from 3 participants. The theory grounded in this study is based on Rogers’ Diffusion of Innovation theory. The results demonstrate that most of them had high perceptions and positive attitude toward integrating the internet in teaching purposes; however, there were some barriers such as low quality of technical support or limited time of class hindered them to utilize the internet for teaching purposes.